Clinical effectiveness of branded versus generic piperacillin-tazobactam for treating severe community-acquired pneumonia - Cheng-Yi Wang; Chia-Hung Chen; Chih-Yen Tu; Wei-Chih Chen; Li-Kuo Kuo; Yao-Tung Wang; Pin-Kuei Fu; Shih-Chi Ku; Wen-Feng Fang; Chin-Ming Chen; Chih-Cheng Lai (Elsevier, 2022)
Purpose: To compare the clinical effectiveness of branded versus generic piperacillin-tazobactam for treating severe community-acquired pneumonia (CAP). Patients and methods: We identified patients with severe CAP who received piperacillin-tazobactam based on a nine-center registry database. Furthermore, we classified the patients in three hospitals, which used only branded piperacillin-tazobactam as the study group, and the patients in six other hospitals, which used both branded and generic products as the control group. Results: A total of 472 patients (n = 263 in the study group and n = 209 in the control group) with severe CAP were included. The study group using branded piperacillin-tazobactam had higher odds of clinical cure (adjusted odds ratio [OR] = 3.77, 95 % confidence interval [CI], 1.93-7.37) and lower odds of treatment failure (adjusted OR = 0.28, 95 % CI, 0.13-0.58) than the control group receiving either branded or generic piperacillin-tazobactam. In addition, the study group was associated with higher odds of clinical effectiveness (adjusted OR = 2.95, 95 % CI, 1.46-6.11), less odds of clinical ineffectiveness (adjusted OR = 0.39, 95 % CI, 0.18-0.81), and lower risk of in-hospital mortality (adjusted OR = 0.39, 95 % CI, 0.21-0.73). Conclusion: Based on the findings of the present study using indirect comparison, the clinical effectiveness of generic piperacillin-tazobactam for treating patients with severe CAP might not be as good as that of brand-name products.